Impactos ambientales y sus efectos en la actividad turística del Sector Ruta del Rio, ciudad Quevedo, año 2021 - Arboleda Mayorga, Maria Alejandra (2021)
The study of the impacts, plans, programs and tourism projects on the environment is essential before making decisions that may be irreversible. Impact studies are multidisciplinary, since it is about knowing the positive and negative aspects that a decision related to an investment for development may have on the natural and social environment in order to take due precautions. The economic development process registered in some rural areas of the country has generated in recent years the intensive occupation of spaces where the most favorable conditions for tourism investment are concentrated. However, it is frequent to observe that tourism is seriously altered by the inadequate management of the territory. The close relationship that exists between conservation of the receiving environment and the growth of tourism activity raises a question for the management of regional and local authorities and for private entrepreneurs linked to the sector: how to make tourism development compatible with the expectations of economic progress of rural communities? The main objective of this work is to propose some methodological guidelines to incorporate the environmental variable in the decisions that affect the investment process in rural tourist areas, taking as a reference the legal framework in force in the country.